Pengaruh Mekanisme Good Corporate Governance dan Struktur Kepemilikan Modal Terhadap Pengungkapan Laporan Keberlanjutan (Sustainbility Report) - Janil Irawan; Enggar Diah Puspa Arum; Misni Erwati (Badan Penerbit STIEPARI Press, 2025)
This study was conducted to see the effect of Good Corporate Governance Mechanism and Capital Ownership Structure on Sustainability Report Disclosure. The good corporate governance mechanism is seen from the number of Audit Committees, Board of Commissioners, and Board of Directors. The capital ownership structure is seen from Managerial Ownership, Institutional Ownership, and Foreign Ownership on the Sustainability Report indicator consisting of Economic, Environmental, and Social indicators. This study uses secondary data sourced directly from documents or files in the form of annual reports or sustainability reports of companies for the 2019-2023 period in energy sector companies listed on the Indonesia Stock Exchange (IDX). Data processing using the Smart-PLS application system with results showing that the Good Corporate Governance Mechanism has a significant positive effect on sustainability report disclosure, and the capital ownership structure has a positive effect on sustainability report disclosure.